Evaluation of Toyocerin®, a probiotic containing Bacillus toyoi spores, on the health status and performance of sows and their litters - GEORGOULAKIS (I.E. ΓΕΩΡΓΟΥΛΑΚΗΣ) I. E.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ) C.; MILIOTIS (Χ. ΜΗΛΙΩΤΗΣ) Ch.; MALANDRAKIS (Ε.Ε. ΜΑΛΑΝΔΡΑΚΗΣ) E. E.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
The aim of this study was to assess the efficacy of Toyocerin®, a probiotic containing l x l09Bacillus toyoi spores per gram, on the health status and productivity of sows and their litters. Eighty gilts and sows were allocated into four experimental groups as follows: TOYO - 0 = control, TOYO - 0.5 = 0.5xl09 Bacillus toyoi spores/kg of feed, TOYO - 1 = l.0xl09Bacillus toyoi spores/kg of feed, TOYO - 2 = 2.0x109Bacillus toyoi spores/kg of feed. The treatments started at the day of service and covered two complete breeding cycles. Toyocerin® supplementation of the feed improved gilt/sow performance by: increasing (P<0.05) the mean body weight from service to farrowing, decreasing (P<0.05) the mean weight loss from farrowing to weaning and decreasing (P<0.05) the mean weaning-to-conception interval. Toyocerin® also showed a positive effect on litter characteristics in terms of: higher (P<0.05) mean number of piglets born alive at each birth, higher (P<0.05) mean number of piglets weaned, a higher (P<0.05) mean piglet body weight at each weaning and lower (P<0.05) mean diarrhoea score. Finally, Toyocerin® tended to improve the health status and fertility of sows demonstrating: a tendency for lower percentages of sows with abnormal clinical signs and a similar effect on the percentages of sows returning to oestrus. These beneficial effects of Toyocerin® were more pronounced in the TOYO - 1 and the TOYO – 2 groups.